2017
DOI: 10.3332/ecancer.2017.715
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastasis risk factors in breast cancer

Abstract: Bone is the single most frequent site for bone metastasis in breast cancer patients. Patients with bone-only metastasis have a fairly good prognosis when compared with patients with visceral disease. Nevertheless, cancer-induced bone disease carries an important risk of developing skeletal related events that impact quality of life (QoL). It is therefore particularly important to stratify patients according to their risk of developing bone metastasis. In this context, several risk factors have been studied, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(81 citation statements)
references
References 100 publications
2
72
1
6
Order By: Relevance
“…With this result, it doesn't relate to a study conducted by Pulido and associates, where they stated that bone was the most common distant metastasis target organ found in breast cancer patients. 16 Similar outcome also presented from a study conducted by Chen, stating that bone was the most common distant metastases target organ in breast cancer patients. 17 Our study showed several patients, particularly patient aged 40 years and above suffered distant metastasis for more than one target organ.…”
Section: Resultssupporting
confidence: 75%
“…With this result, it doesn't relate to a study conducted by Pulido and associates, where they stated that bone was the most common distant metastasis target organ found in breast cancer patients. 16 Similar outcome also presented from a study conducted by Chen, stating that bone was the most common distant metastases target organ in breast cancer patients. 17 Our study showed several patients, particularly patient aged 40 years and above suffered distant metastasis for more than one target organ.…”
Section: Resultssupporting
confidence: 75%
“…Patients with bone as a single metastatic site demonstrate a better prognosis than those with visceral or both bone and visceral disease [49] . Visceral metastases, those occurring in the soft internal organs of the body, including the lungs, heart, and organs of the digestive, excretory, reproductive, and circulatory systems, portend a poor prognosis [2,50] .…”
Section: Treatment In the Setting Of Visceral Diseasementioning
confidence: 98%
“…For this purpose, emerging studies have highlighted a significant association between molecular subtype of BCawhich reflect phenotypic and genotypic variations of the biology of this tumour, and risk of bone metastasis. 29,30 For instance, some of these studies have shown that patients with Luminal A type BCa were prone to metastasizing to the bone rather than to other anatomical sites. 30 Furthermore, hormone receptor (HR + )/human epidermal growth factor receptor (HER2 + )(HR + /HER2 + ) subtype significantly correlated with an elevated risk of bone metastasis.…”
Section: Osteoclast and Osteoblast As Therapeutic Targetmentioning
confidence: 99%
“…30 Conversely, patients with a triple-negative subtype (TNBC) were, most likely to develop visceral metastases rather than bone metastasis. 29,30 On the other hand, the use of multi-OMICS integrative approaches has greatly facilitated the identification of a growing number of molecular candidates which appear to be promising as potential diagnostic and prognostic biomarkers to identify BCa patients at high risk of developing bone metastasis. 13,22,29 In summary, the currently available clinical approach to patients with BCa-related bone disease is mostly palliative.…”
Section: Osteoclast and Osteoblast As Therapeutic Targetmentioning
confidence: 99%